Biochemistry and Molecular Biology of Gelatinase B or Matrix Metalloproteinase-9 (MMP-9) - Van den Steen, Philippe E.; Dubois, Bénédicte; Nelissen, Inge; Rudd, Pauline M.; Dwek, Raymond A.; Opdenakker, Ghislain (Critical reviews in biochemistry and molecular biology, 2002)
The matrix metalloproteinases (MMPs) form an enzyme family of which gelatinase B (MMP-9) represents the largest and most complex member. We focus here on the biochemical properties, regulation, and functions of gelatinase B. The tight regulation of gelatinase B activity is highly complex and is established at five different levels. The transcription of the gelatinase B-gene depends on various cis-elements in its gene promotor and is induced or repressed by a large variety of soluble factors, including cytokines, growth factors, and hormones and by cellular contacts acting through specific signaling pathways. The specific regulation of its secretion occurs in cells storing gelatinase B in granules. After secretion, progelatinase B must be activated through an activation network. The enzyme activity is further regulated by inhibition and by other mechanisms, such as fine-tuning and stabilization by glycosylation. The ability of gelatinase B to degrade components of the extracellular matrix and to regulate the activity of a number of soluble proteins confers an important role in various physiological and pathological processes. These include reproduction, growth, development, inflammation, and vascular and proliferative diseases.